Magnetic crack-based piezoinductive mechanical sensors: way to extreme robustness and ultra-sensitivity - Yulian Peng; Zhengyan Wang; Houping Wu; Junchen Luo; Xinxin Chang; Yufeng Wang; Shiwu Zhang; Zhihua Feng; Unyong Jeong; Hongbo Wang (Nature Communications)
Abstract Soft mechanical sensors with high performance, mechanical robustness, and manufacturing reproducibility are crucial for robotics perception, but simultaneously satisfying these criteria is rarely achieved. Here, we suggest a magnetic crack-based piezoinductive sensor (MC-PIS) which exploits the strain modulation of magnetic flux in cracked ferrite films. The MC-PIS is insensitive to fatigue-induced crack propagation and environmental changes, showing same performance even when scratched in half or run over by a car. It can detect bidirectional bending with a precision of 0.01° from −200° to 327°, allowing for real-time reconstruction of dynamic shape changes of a flexible ribbon. We demonstrate an artificial finger recognizing surface topology and musical notes via vibrations, a crawling robot responding appropriately to external stimuli, a tree-planting gripper performing consecutive tasks from digging soil, removing stones, to placing trees. The MC-PIS opens a new paradigm to develop ultrasensitive yet highly robust sensors in real-world robotics applications.